Pertimbangan Hakim dalam Menjatuhkan Pidana terhadap Prajurit yang Melakukan Ketidakhadiran Tanpa Izin dalam Waktu Damai (Analisis Yuridis Putusan Peradilan Militer Nomor 41-K/PM.III-13/AD/XI/2025) - Wahyuningrum, Ardila Lintang; Subadi, Subadi; Nugroho, Sigit Sapto (Lembaga Teewan Journal Solutions, 2026)
Absence without leave during peacetime constitutes a violation of military discipline that can undermine readiness, organizational effectiveness, and the core duties of the Indonesian National Armed Forces (TNI). Accordingly, punishment for soldiers who breach these rules must be firm while still upholding the principles of justice, legal certainty, and benefit. This study examines how judges weighed the factors underlying the sentencing of a soldier for unauthorized absence during peacetime, based on Military Court Decision Number 41-K/PM.III-13/AD/XI/2025, and assesses whether these considerations align with applicable military criminal law. The research employs normative legal methods through statutory, conceptual, and case approaches, drawing on primary legal materials such as the Military Criminal Code, Law Number 31 of 1997 on Military Courts, and Law Number 34 of 2004 on the TNI, alongside secondary sources including books and scientific journals. Unlike previous studies that generally discuss the application of Article 87 of the Military Criminal Code in a broad context, this research specifically analyzes the judges' legal reasoning (ratio decidendi) in Military Court Decision Number 41-K/PM.III-13/AD/XI/2025 and evaluates its conformity with the objectives of military law enforcement and discipline. The findings show that judges assessed the fulfillment of criminal elements, the validity of evidence, trial facts, and aggravating or mitigating conditions, while also weighing social and philosophical values to preserve discipline and deterrence. The decision's considerations were largely consistent with military criminal law and law-enforcement principles, though greater consistency in sentencing remains necessary to ensure fairness across similar cases.